Legal Dynamics of Divorce, Transformation of Social Structure, and Protection of Women-Children in the Family Regulatory System - Sayuti; Aliyah, Nelud Darajaatul; Mardikaningsih, Rahayu (Journal of Social Science Studies, 2023)
The current dynamics of divorce law have brought fundamental changes to the patterns and social structures of modern society. Through a thematic analysis of the literature, this study examines how the implementation of the Marriage Law and related regulations has encouraged the transformation of family structures and redefined the social roles of women and children after divorce. This study finds that the implementation of the law often faces challenges in providing substantive justice, mainly due to gender inequality, weak legal knowledge, and the persistence of patriarchal norms. The impact of divorce on children includes decreased emotional stability, challenges in education, and limited access to social support. For women, divorce presents economic risks and social stigma, although it also opens up opportunities to build new social agency. This research emphasizes the importance of integrating premarital education programmed, reforming the legal system, and strengthening community support as collective strategies to deal with the disruption of social structures after divorce. This study recommends that the state and society reorganize the social protection system based on substantive justice to ensure that women and children receive optimal rights and protection in an ever-changing social landscape. The results of this study are expected to serve as a strategic reference for policymakers, educators, and social actors to strengthen the resilience of families and communities in a sustainable manner.